Analisis Hubungan Karakteristik Individu terhadap Kejadian Infeksi Menular Seksual pada Wanita Pekerja Seks di Kota Kupang - Sirait, Tupak; Roga, Anderias Umbu; Ratu, Jacob; Sembiring, Anita Christina (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Background: Sexually transmitted infections are diseases that are transmitted through sexual intercourse with partners who have high-risk sexual behavior, one of which is changing sex partners without using condoms. This behavior is most likely to occur by using the services of female sex workers. Objective: this study aims to analyze the factors associated with the incidence of sexually transmitted infections among female sex workers in Kupang City. Method: this study is a quantitative study with a cross sectional design. Results: bivariate analysis showed that the variables of individual characteristics (age, education, length of work as a female sex worker, and income) and prevention behavior of sexually transmitted infections (condom use) had a p value <0.25. After multivariate analysis, it was found that the variables of length of work and condom use had a p value <0.05. Conclusion: there is an association between individual characteristics (age, education, length of time working as a female sex worker, and income) and sexually transmitted infection prevention behavior (condom use) with the incidence of sexually transmitted infections. The variables of length of employment and condom use were significantly associated with the incidence of sexually transmitted infections among female sex workers in Kupang City.